Droplet entrainment analysis of three-phase low liquid loading flow. (March 2017) - Karami, Hamidreza; Pereyra, Eduardo; Torres, Carlos F.; Sarica, Cem
Highlights: Three-phase flow tests were conducted to analyze droplet entrainment in gas phase. Effects of vSL, vSg, inlet WC, and MEG presence in aqueous phase were analyzed. Available two-phase flow correlations were compared to the data and analyzed. A correlation was proposed for two-phase flow entrainment in horizontal pipes. A method was proposed to predict three-phase entrainment based on two-phase case. Abstract: Most of the commonly used multiphase flow models neglect the amount of droplets entrained in stratified wavy flow. However, the experimental data presented in this study show high entrainment values, exceeding 50% in some cases. This shows that neglecting entrainment phenomenon can introduce a major source of discrepancy into multiphase flow modeling predictions. This study improves the entrainment fraction predictions in three-phase stratified flow. The droplet entrainment in three-phase stratified flow in horizontal pipelines is experimentally investigated using a 0.152-m ID facility. The experiments are conducted under low liquid loading conditions, which is very commonly observed in wet gas pipelines. The oil-aqueous-gas flow experiments are initially performed without mono-ethylene glycol (MEG), and then repeated with 50 wt% of MEG in the aqueous phase to analyze the effects of MEG presence on entrainment. MEG is a commonly used inhibitor in oil industry, applied to avoid hydrate formation in offshore systems. Its impacts on multiphase flow droplet entrainment are investigated. The experimental range of this study covers superficial gas velocity ( vSg ) values from 17 to 23 m/s, superficial liquid velocity ( vSL ) values of 0.01 and 0.02 m/s, and inlet liquid stream aqueous phase fraction ( APFin ) values between 0 to 100%. Similar test matrix is completed for both water and water and MEG solution as the aqueous phase. An isokinetic probe system is used to measure the entrained droplet flux at different vertical positions in the gas phase. Liquid entrainment fraction is then estimated by means of volumetric averaging. The trends of the data with respect to input parameters are investigated. The two and three-phase entrainment fraction data are used for a correlation evaluation study. Performances of ten correlations for two-phase entrainment fraction are compared to the experimental data, and best performing correlations are identified. The correlation of Pan and Hanratty (2002) is modified in an effort to improve the entrainment fraction estimations. The predictions of the modified correlation are compared with the acquired data and datasets from the literature. In addition, a simple empirical correlation is proposed to predict liquid phase entrainment fraction for three-phase flow systems.